The impact of program design and coaching support on novice teachers' induction experience. Issue 2 (15th March 2021) - Kwok, Andrew; Mitchell, Douglas; Huston, Debbee
ABSTRACT: Program surveys of over 2, 000 novice teachers and 1, 000 of their reflective coaches are analyzed to explore the impact of induction, generally, and coaching, specifically, on two program outcomes. Using Exploratory Structural Equation Modeling, we find that certain induction structures, aspects of coaching activities, and teacher-coach match characteristics can have an impact on professional learning and teacher pedagogical success. Findings have implications for induction program design and the impact teacher coaching can have in professional development.